Whole-body vibration and the prevention and treatment of delayed-onset muscle soreness - Aminian-Far, A.; Hadian, M.-R.; Olyaei, G.; Talebian, S.; Hoshang Bakhtiary, A. (Journal of Athletic Training, 2011)
Context: Numerous recovery strategies have been used in an attempt to minimize the symptoms of delayed-onset muscle soreness (DOMS). Whole-body vibration (WBV) has been suggested as a viable warm-up for athletes. However, scientific evidence to support the protective effects of WBV training (WBVT) on muscle damage is lacking.